Swedish Multinational Corporations: Recent Trends in Foreign Activities - Pontus Braunerhjelm; Karolina Ekholm; Lennart Grundberg; Patrik Karpaty (The Research Institute of Industrial Economics (IUI), 1996)
This paper presents recent trends in the foreign activities of Swedish multinationals. The focus is on the distribution of production and R&D between the MNCs' domestic and foreign units, and the pattern of trade within the firms. Issues concerning entry modes and the importance of information technology in coordinating geographically dispersed production are also highlighted. Despite considerable improvements in the conditions for industrial activities in Sweden, the trend towards increased internationalization of Swedish firms has continued. After a noticeable increase in the share of foreign production located in the former European Community between 1986 and 1990, the recent development suggests a return to a regional distribution of foreign activities similar to the one prevailing in 1986. In the 1990s the increase in foreign production by Swedish MNCs has been concentrated to the NAFTA-countries, Asia and Eastern Europe. Another striking result is the pronounced increase in the share of foreign R&D that has taken place between 1990 and 1994.This paper presents recent trends in the foreign activities of Swedish multinationals. The focus is on the distribution of production and R&D between the MNCs' domestic and foreign units, and the pattern of trade within the firms. Issues concerning entry modes and the importance of information technology in coordinating geographically dispersed production are also highlighted. Despite considerable improvements in the conditions for industrial activities in Sweden, the trend towards increased internationalization of Swedish firms has continued. After a noticeable increase in the share of foreign production located in the former European Community between 1986 and 1990, the recent development suggests a return to a regional distribution of foreign activities similar to the one prevailing in 1986. In the 1990s the increase in foreign production by Swedish MNCs has been concentrated to the NAFTA-countries, Asia and Eastern Europe. Another striking result is the pronounced increase in the share of foreign R&D that has taken place between 1990 and 1994.
Keywords: F23; O32; 330; TRANSNATIONAL CORPORATIONS; RESEARCH AND DEVELOPMENT; Multinationales Unternehmen; Schweden